GSYM : thm -> thm

SYNOPSIS
Reverses the first equation(s) encountered in a top-down search.

DESCRIPTION
The inference rule GSYM reverses the first equation(s) encountered in a top-down search of the conclusion of the argument theorem. An equation will be reversed iff it is not a proper subterm of another equation. If a theorem contains no equations, it will be returned unchanged.
    A |- ..(s1 = s2)...(t1 = t2)..
   --------------------------------  GSYM
    A |- ..(s2 = s1)...(t2 = t1)..

FAILURE CONDITIONS
Never fails, and never loops infinitely.

EXAMPLE
  # ADD;;
  val it : thm = |- (!n. 0 + n = n) /\ (!m n. SUC m + n = SUC (m + n))

  # GSYM ADD;;
  val it : thm = |- (!n. n = 0 + n) /\ (!m n. SUC (m + n) = SUC m + n)

SEE ALSO
NOT_EQ_SYM, REFL, SYM.